The Influence of Service Quality and Promotion on Customer Satisfaction - Muhammad Yusuf; Hendra Suwardana; Kholisatun Nikmah (Universitas Muhammadiyah Gresik, 2024)
This research aims to test and analyze the influence of service quality and promotion on customer satisfaction at KSPPS BMT Terate Palang Tuban. The population or subjects in this research are KSPPS BMT Terate Palang Tuban customers for the last three years with a population of 2,510 customers. The sample used was 96 respondents using random sampling technique. The instrument used in the form of a questionnaire was measured using a Likert scale. The testing technique uses the Validation and Reliability Test, Classic Assumption Test (normality, heteroscedasticity and multicollinearity test), Hypothesis Test which is analyzed using multiple linear regression and the Determinant Coefficient or R test. The research results show that the instrument test results for all variables are valid and reliable. Likewise, all data fulfills classical assumptions. The final results show that there is a positive and significant influence between service and promotion on customer satisfaction. Based on the partial test (t test) shows that the service quality variable has a partial positive and significant effect on customer satisfaction. The promotion variable shows that there is a positive and significant effect on customer satisfaction. Based on the simultaneous test of service quality and promotion, there is a joint influence on customer satisfaction. From these results, all the hypothesized variable relationship arguments are accepted. These results provide input to the bank that service and promotion should be instruments in increasing customer satisfactionKey words: service quality, promotion, customer satisfaction